In-situ observation of temperature effect on the tensile deformation behavior in laser melting deposited TA15 alloy. Issue 3 (April 2021) - Rizwan, Muhammad; Lu, Junxia; Ullah, Rafi; Zhang, Yuefei
Abstract: In this study, laser melting deposited TA15 alloy was examined by in-situ SEM tensile deformation at a range of temperatures; RT, 300℃ and 500℃. The as-fabricated microstructure consists of prior β grains boundaries and fine basketweave microstructure. Due to LMD fabricated alloys' anisotropic behavior, the tested samples were collected from the same region and direction. The XRD and SEM results showed that the temperature up to 500℃ has no impact on the phase constituent and structure morphology, revealing a stable microstructure. The tensile deformation at room temperature (RT) revealed that slip lines were the primary deformation mechanism generated in the parallel and larger alpha grain. An increase in temperature triggered grain boundary sliding during deformation, which enhanced the elongation in the material at the cost of tensile strength reduction. The grain boundary resistance to dislocation slip was affected by the sliding phenomenon due to increased temperature. Overall, the material showed stable tensile characteristics related linearly to the temperature variation.